Successful Laparoscopic Removal of a Self-Inflicted Thermometer that Spontaneously Migrated into the Peritoneal Cavity - Bogdanovic, Jovo; Sekulic, Vuk; Kokovic, Tijana; Djozic, Senjin; Vulin, Dragan (Urology Journal, 2017)
A sixty-three-year-old Caucasian male was referred to emergency service 10 hours after self-infliction of a mercury glass thermometer into the urethra. The patient presented without abdominal or voiding symptoms. Radiological imaging confirmed the presence of a thermometer in the peritoneal cavity, without signs of contrast leakage from the bladder. The patient underwent suture of the perforation site with a subsequent successful removal of the foreign body using laparoscopic approach. Recovery was uneventful. To the best of our knowledge, we are not aware of any previous report of laparoscopic removal of a mercury glass thermometer from the peritoneal cavity. Laparoscopic removal of fragile items, such as a thermometer, is obviously feasible but associated with substantial risks.